The new southern novel: a bibliographical assay - Robert F. Kiernan (Ilha do Desterro)
Any attempt to chronicle the contemporary southern novel is beset by troublesome, interlocking questions. Is the very existence of the genre presumptive? If not, does its tradition continue to instill a sectional awareness among writers flourishing in the last years of the twentieth century? If so, is it not the case that to read any literary text as a mimetic expression of a geographical region is to confine each to the other and to ignore the quiddity of both?